2020
DOI: 10.5588/ijtld.19.0588
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knee extensor and flexor function using isokinetic test in COPD: impact on exercise capacity

Abstract: OBJECTIVE: To quantify the relationship between strength and endurance of knee extensor and flexor and exercise capacity in patients with chronic obstructive pulmonary disease (COPD).METHODS: A total of 108 patients with stable COPD (age: 65 years, IQR25–75: 59–72) were enrolled in this cross-sectional study. Knee extensor and flexor function was evaluated using the isokinetic test, and the parameters attained were considered as independent variables. Exercise capacity was evaluated using 6-minute walking tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The existence of dyspnea in COPD decreases physical activity, and the decrease in physical activity induces and accelerates skeletal muscle dysfunction, worsening the dyspnea in patients, forming a vicious cycle that causes further deconditioning on COPD ( 7 ). Recently, lower limb muscle function has been associated with exercise capacity in COPD ( 8 ). Previous studies have confirmed that skeletal muscle dysfunction is an additional important contributor to COPD exercise restriction and function impairments ( 9 , 10 ), and it is closely related to the quality of life, readmission rate, and mortality ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The existence of dyspnea in COPD decreases physical activity, and the decrease in physical activity induces and accelerates skeletal muscle dysfunction, worsening the dyspnea in patients, forming a vicious cycle that causes further deconditioning on COPD ( 7 ). Recently, lower limb muscle function has been associated with exercise capacity in COPD ( 8 ). Previous studies have confirmed that skeletal muscle dysfunction is an additional important contributor to COPD exercise restriction and function impairments ( 9 , 10 ), and it is closely related to the quality of life, readmission rate, and mortality ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%